Sanitation and modernity on a Remote Island: A study of community behavior toward hygienic latrine use in Pengikik Island - Ayu Lestari; Rahma Syafitri; Nikodemus Niko (Privietlab, 2025)
This study explores the transformation of community behavior regarding the use of hygienic latrines in Pengikik Village, a remote island community with historically poor sanitation practices. Inadequate latrine management contributes significantly to environmental degradation. Promoting the widespread use of healthy latrines, which are facilities designed for safe and sanitary human waste disposal, is a key strategy for improving public health. Using a phenomenological framework design, the research draws on data from six purposively selected informants through semi-structured interviews. The analysis employs Peter L. Berger and Thomas Luckmann’s theory of social construction to examine behavioral changes. The findings indicate that 19 out of 53 households have constructed private healthy latrines, and eight communal units have been built with septic systems. Behavioral change occurred through three interrelated processes: targeted socialization and education by health workers, gradual internalization of hygienic practices, and normalization of latrine use in daily life. These processes have reshaped community perceptions, fostering a collective understanding of the importance of sanitary facilities in the community. As a result, the community has shifted away from open defecation and toward the consistent use of healthy latrines.